Eksplorasi Persepsi Konsumen Melalui Studi Komparatif Suasana Toko Indomaret dan Alfamart - Octavini, Nanda Andreas; Wardana, M. Azka Kesuma (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Indomaret and Alfamart are two of the largest retail chains in Indonesia, competing fiercely in the minimarket sector. The store atmosphere is a key factor influencing customer attraction and loyalty. This study aims to compare consumer perceptions of the store atmosphere between Indomaret and Alfamart in Bandar Lampung city. This research uses the probability sampling method with cluster random sampling technique. The sample size used is 384 respondents from various areas in Bandar Lampung. Data analysis is conducted using descriptive statistics and independent sample t-test. The results indicate no significant difference in attributes such as lighting, sound, layout, temperature, technology, and accessibility between Indomaret and Alfamart. However, there are significant differences in attributes such as color, aroma, staff behavior, and decoration, with Alfamart scoring higher in color, staff behavior, and decoration, while Indomaret excels in aroma. The store atmosphere significantly impacts consumer perceptions and shopping experiences. Indomaret and Alfamart need to focus on enhancing store atmosphere elements according to consumer preferences to increase competitiveness and customer loyalty